The Effect of Sugar Apple (Annona squamosa L.) Seeds Solution as an Insecticide Against Mortality of Aedes aegypti Mosquito with Liquid Electric Method - Amalinda Mega Novasari; Retno Sasongkowati (JURNAL KESEHATAN LINGKUNGAN, 2017)
Dengue hemorrhagic fever is a public health problem in Indonesia that the number of DHF cases has been increased. Morbidity number of DHF per 100,000 population at 2011 was 26.67 became 34.3 in 2012. The control of DHF has been attempted, but a lot of synthetic insecticide used has been negatively affected to environment. So, it need the insecticide alternative. The aim of study was to identify the effect of solvent sugar apple (Annona squamosa L.) seeds to the death of Aedes aegypti mosquitoes by electric liquid method. Type of this research was experimental with cross sectional study design as well as the post test only control group design. The study was conducted from February to July 2013 in the Laboratory of Entomology of the Provincial Health Office of East Java. The population of this research was the Aedes aegypti with 560 sample of mosquitoes were divided into five treatments and four repetitions for each treatment. The collection of quantitative data drawn from primary data through observation by calculating the death of Aedes aegypti of each the sugar apple seeds concentration of 10%, 20%, 30%, 40% and 50% for 24 hours. The results showed that the concentration of 50% solvent of sugar apple seeds provide the greatest effect in causing the death of Aedes aegypti mosquitoes as many as 36 died after exposure. It can be concluded that there are effected by giving solvent of sugar apple (Annona squamosa L.) seeds to the death of Aedes aegypti mosquitoes by electric liquid method.